Analisis Faktor Yang Mempengaruhi Kepuasan Pasien BPJS Terhadap Kualitas Pelayanan Rawat Jalan Di RSI Malahayati Medan - Nurcholisah Fitra (STIKES Columbia Asia Medan, 2026)
Patient satisfaction is a key indicator of health service quality in the National Health Insurance era. Outpatient services for BPJS members still face problems regarding waiting time, communication, and facilities. This study aimed to analyze factors affecting BPJS patient satisfaction with outpatient service quality at Malahayati Islamic Hospital Medan in 2026. A cross-sectional analytic design was applied to 150 respondents selected through consecutive sampling. Data were collected using a validated questionnaire (r>0.361; α=0.876) and analyzed by Chi-square and multiple logistic regression. Results showed that waiting time (p<0.001), staff competence (p<0.001), staff attitude (p<0.001), drug availability (p=0.032), facility comfort (p<0.001), administrative ease (p=0.003), and information clarity (p=0.008) were significantly associated with satisfaction. Multivariate analysis revealed waiting time as the most dominant factor (OR=5.42; 95% CI: 2.31–12.71), followed by staff competence (OR=4.18), facility comfort (OR=2.87), and staff attitude (OR=2.42), with Nagelkerke R²=0.512. Hospital management should optimize service flow and adopt digital queuing systems to enhance patient satisfaction.